Impact of patient characteristics on ASDAS disease activity state cut-offs in axial spondyloarthritis: results from nine European rheumatology registries - Bente Glintborg; Merete Lund Hetland; Tore K Kvien; Brigitte Michelsen; Dan Nordström; Karel Pavelka; Ziga Rotar; Maria Jose Santos; Anne Gitte Loft; Ana Rodrigues; Mikkel Østergaard; Jakub Zavada; et al. (RMD Open)
Objectives To re-evaluate cut-offs for disease activity states according to the Axial Spondyloarthritis Disease Activity Score (ASDAS), and study the impact of sex, age, calendar time, disease and symptom duration on ASDAS and ASDAS cut-offs in a large contemporary cohort.Methods Data from 2939 patients with axial spondyloarthritis (axSpA) starting their first tumour necrosis factor inhibitor in nine European registries were pooled and analysed. Receiver operating characteristic analyses were performed to identify cut-offs against external criteria. Six-month data including patient and physician global assessments, both ≤1 (0–10 integer scale), and Assessment of SpondyloArthritis International Society partial remission were used for separation of inactive disease (ID) from low disease activity (LDA), while patient and physician global ≤3 were applied as external criteria to separate LDA from high disease activity (HDA). Patient and physician global ≥6 were applied to separate HDA from very high disease activity in baseline data.Results The three ASDAS cut-offs identified to separate the four disease activity states in the overall patient population were <1.3, <2.0 and >3.5. Cut-offs for ID and LDA in women were higher (<1.5 and <2.0, respectively) than in men (<1.3 and <1.9), as were cut-offs in patients ≥45 years (<1.5 and <2.2) versus ≤34 years (<1.2 and <1.9) and 35–44 years (<1.3 and <1.8). Cut-offs were independent of calendar time and disease duration.Conclusions Re-evaluation of ASDAS cut-offs for disease activity states in a large multi-national axSpA cohort resulted in cut-offs similar to those currently endorsed. Differences in cut-offs between sex and age groups for ID and LDA were observed, but the differences were minor.